Mindfulness and situational interest. Issue 3 (16th March 2019) - Grund, Axel; Schäfer, Nina; Sohlau, Sylvia; Uhlich, Janne; Schmid, Sebastian
Abstract: In an attempt to exploit the concept of mindfulness for educational contexts, we investigated the role of dispositional mindfulness as an internal resource for the development of situational interest. Using an online questionnaire, we assessed participants' ( N = 161, mean age = 30.4 years, 74% female, 66% university students) mindfulness, presented them with a text on bionics, and asked them to indicate their situational interest regarding the material (t1). One week later, they indicated their maintained situational interest (t2). Findings reveal a positive relationship between mindfulness and situational interest at t1, especially with regard to participants' ability to be momentarily 'present' and affective aspects of situational interest. Furthermore, we found an indirect effect of mindfulness on maintained situational interest at t2 via participants' interest at t1. These findings were independent from participants' initial interest and knowledge. Contrary to our expectation, we did not find a moderation effect for mindfulness on the relation between situational interest at t1 and t2. We discuss these findings in terms of implications for formal learning contexts.